Back pain, disability, and radiographic vertebral fracture in European women: a prospective study. - O'Neill, T; Cockerill, W; Matthis, C; Raspe, H; Lunt, M; Cooper, C; Banzer, D; Cannata, J; Naves, M; Felsch, B; Felsenberg, D; Janott, J; et al. (2004)
Vertebral fractures are associated with back pain and disability. There are, however, few prospective data looking at back pain and disability following identification of radiographic vertebral fracture. The aim of this analysis was to determine the impact of radiographically identified vertebral fracture on the subsequent occurrence of back pain and disability. Women aged 50 years and over were recruited from population registers in 18 European centers for participation in the European Prospective Osteoporosis Study. Participants completed an interviewer-administered questionnaire which included questions about back pain in the past year and various activities of daily living, and they had lateral spine radiographs performed. Participants in these centers were followed prospectively and had repeat spine radiographs performed a mean of 3.7 years later. In addition they completed a questionnaire with the same baseline questions concerning back pain and activities of daily living. The presence of prevalent and incident vertebral fracture was defined using established morphometric criteria. The data were analyzed using logistic regression with back pain or disability (present or absent) at follow-up as the outcome variable with adjustment made for the baseline value of the variable. The study included 2,260 women, mean age 62.2 years. The mean time between baseline and follow-up survey was 5.0 years. Two hundred and forty participants had prevalent fractures at the baseline survey, and 85 developed incident fractures during follow-up. After adjustment for age, center, and the baseline level of disability, compared with those without baseline prevalent fracture, those with a prevalent fracture (odds ratio [OR] = 1.4; 95% confidence interval [CI] 1.0 to 2.0) or an incident fracture (OR = 1.7; 95% CI, 0.9 to 3.2) were more likely to report disability at follow-up, though the confidence intervals embraced unity. Those with both a prevalent and incident fracture, however, were significantly more likely to report disability at follow-up (OR = 3.1; 95% CI, 1.4 to 7.0). After adjustment for age, center, and frequency of back pain at baseline, compared with those without baseline vertebral fracture, those with a prevalent fracture were no more likely to report back pain at follow-up (OR = 1.2; 95% CI, 0.8 to 1.7). There was a small increased risk among those with a preexisting fracture who had sustained an incident fracture during follow-up (OR = 1.6; 95% CI, 0.6 to 4.1) though the confidence intervals embraced unity. In conclusion, although there was no significant increase in the level of back pain an average of 5 years following identification of radiographic vertebral fracture, women who suffered a further fracture during follow-up experienced substantial levels of disability with impairment in key physical functions of independent living.